Pengaruh Moral Pajak, Layanan Pajak dan Persepsi Efektivitas Digitalisasi Pajak Terhadap Kepatuhan Membayar Pajak PPH Orang Pribadi Pada KPP Pratama Medan Timur - Syafitri, Audyna; Izzah, Nurul (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study employed quantitative research. Data sources used were primary and secondary sources. Data collection techniques included questionnaires, interviews, and documentation. Data analysis techniques used were descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The sample size for this study was 100 respondents. Based on the partial test results, it was found that the implementation of tax morale had a positive and significant effect on tax compliance (t-value 2.463 > t-table 1.984). Furthermore, tax services had a positive and significant effect on tax compliance (t-value 4.184 > t-table 1.984). Digitalization did not have a positive and significant effect on tax compliance (t-value 1.178 < t-table 1.984). Based on the results of the simultaneous test, it was found that the implementation of tax morale (X1), tax services (X2), and tax digitalization (X3) collectively had a positive and significant effect on tax compliance at the Medan Timur Pratama Tax Office (KPP Pratama).